The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1104/pp.84.4.1408
|View full text |Cite
|
Sign up to set email alerts
|

Solute Accumulation in Tobacco Cells Adapted to NaCl

Abstract: Cells of Nicotiana tabacum L. var Wisconsin 38 adapted to NaCi (up to 428 millimolar) which have undergone extensive osmotic adjustment accumulated Na' and a-as principal solutes for this adjustment. Although the intracellular concentrations of Na' and a-correlated well with the level of adaptation, these ions apparently did not contribute to the osmotic adjustment which occurred during a culture growth cycle, because the concentrations of Na' and a-did not increase during the period of most active osmotic adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
3

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 162 publications
(96 citation statements)
references
References 23 publications
5
86
0
3
Order By: Relevance
“…The activity of V. aconitifolia P5CS is reduced to 50% by 6 mm Pro (Hu et al, 1992). Plant cells under osmotic stress can accumulate up to 129 mm Pro in the cytosol (Binzel et al, 1987;, a concentration that would almost completely turn off the P5CS enzyme. This is contradictory to the fact that plants under stress continue to synthesize Pro and build up the Pro pool.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of V. aconitifolia P5CS is reduced to 50% by 6 mm Pro (Hu et al, 1992). Plant cells under osmotic stress can accumulate up to 129 mm Pro in the cytosol (Binzel et al, 1987;, a concentration that would almost completely turn off the P5CS enzyme. This is contradictory to the fact that plants under stress continue to synthesize Pro and build up the Pro pool.…”
Section: Discussionmentioning
confidence: 99%
“…The extracts were frozen, lyophilized, and resuspended in 1 ml of H2O. Na+ and Cl-were measured as described previously (2). The radioactivity in the media samples and cell extracts was determined with a Beckman LS6800 liquid scintillation counter in 4 ml of aqueous counting cocktail (Aquasol, Amersham).…”
Section: Methodsmentioning
confidence: 99%
“…Na+ and Cl-, the principal components of the extensive osmotic adjustment exhibited by these cells, accumulated to an average whole cell concentration of 500 and 400 mm, respectively (2). Presented in this paper are results of an investigation utilizing steady state efflux kinetic analysis and scanning electron energy dispersive xray microanalysis to identify the intracellular localization of Na + and Cl-accumulated by cells adapted to 428 mM NaCl.…”
mentioning
confidence: 99%
“…Unadapted tobacco (So) cells are usually plasmolyzed in 0.3 M NaCI, and spherical protoplasts, or convex membrane orientations, are observed within the cell wall (Figure la). Tobacco cells adapted to grow in medium containing 428 mM NaCl (S25) are osmotically adjusted and require more concentrated solutions to plasmolyze them (Binzel et al, 1985;lraki et al, 1989). Only after exposure to solutions much greater than 1 M do the plasma membranes pull away from their walls.…”
Section: Plasma Membrane-cell Wall Adhesion In Naci-adapted Cellsmentioning
confidence: 99%
“…Additional isolines have since been selected that grow in as high as 3.5% NaCI. The adapted cells (S25) have a drastically altered growth physiology that results in much slower cell expansion, with fully expanded cells having volumes only one-fifth to one-eighth those of unadapted So cells (Binzel et a/., 1987). Several metabolic alterations have been identified that contribute to adaptation to the NaCl (Bressan eta/., 1987), and several alterations in the physical and chemical structure of the cell wall were identified as possible determinants of the altered tensile strength and extensibility associated with the severe growth limitation despite adequate turgor pressure (Iraki eta/., 1989).…”
Section: Cell Culturesmentioning
confidence: 99%